Dinamika Perkembangan Bahasa dan Sastra dalam Konteks Globalisasi - Ni Putu Andini Desiyanti Laksmi; I Nyoman Bawa Bagiada (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Globalization has brought significant impacts across various sectors of life, including language and literature. Rapid flows of information, intercultural interactions, and the dominance of international languages such as English have triggered changes, adaptations, and even identity confusion in the use of local languages and the development of literary works. This paper explores the influence of globalization on the evolution of language and literature, both in the context of preservation and creativity. Language undergoes modifications in structure and vocabulary as a result of cultural interaction and technological advancement, while literature evolves in terms of genres and media, as reflected in the emergence of digital literature and literacy phenomena on social media platforms. On the other hand, globalization also provides opportunities for local literary works to reach international audiences through translation and digital media. Using a descriptive and analytical approach, this paper highlights the challenges and opportunities arising from the intersection of globalization, language, and literature, as well as their significance in formulating strategies to maintain cultural identity through language and literary expression.